An artificial self‐sufficient cytochrome P450 directly nitrates fluorinated tryptophan analogs with a different regio‐selectivity. Issue 5 (4th February 2016) - Zuo, Ran; Zhang, Yi; Huguet‐Tapia, Jose C.; Mehta, Mishal; Dedic, Evelina; Bruner, Steven D.; Loria, Rosemary; Ding, Yousong
Abstract: Aromatic nitration is an immensely important industrial process to produce chemicals for a variety of applications, but it often suffers from multiple unsolved challenges. Enzymes as biocatalysts have been increasingly used for organic chemistry synthesis due to their high selectivity and environmental friendliness, but nitration has benefited minimally from the development of biocatalysis. In this work, we aimed to develop TxtE as practical biocatalysts for aromatic nitration. TxtE is a unique class I cytochrome P450 enzyme that nitrates the indole ofl ‐tryptophan. To develop cost‐efficient nitration processes, we fused TxtE with the reductase domains of CYP102A1 (P450BM3) and of P450RhF to create class III self‐sufficient biocatalysts. The best engineered fusion protein was comparable with wild type TxtE in terms of nitration performance and other key biochemical properties. To demonstrate the application potential of the fusion enzyme, we nitrated 4‐F‐dl ‐tryptophan and 5‐F‐l ‐tryptophan in large scale enzymatic reactions. Tandem MS/MS and NMR analyses of isolated products revealed altered nitration sites. To our knowledge, these studies represent the first practice in developing biological nitration approaches and lay a solid basis to the use of TxtE‐based biocatalysts for the production of valuable nitroaromatics. Abstract : Aromatic nitration is among the most important chemical reactions in industry but has not been benefited from the rapid development of biocatalysis. The current study engineers a novel self‐sufficient P450 biocatalyst to nitrate fluoro‐tryptophan analogs in an earth‐friendly manner and reveals unusual enzyme regio‐flexibility controlled by substrates, paving the way for the development of green nitration processes.